A basic approach to the verification and validation of sorption isotherm models - Lutovska Monika; Pavkov Ivan; Mijakovski Vladimir; Stamenkovič Zoran (Journal on Processing and Energy in Agriculture, 2018)
In this paper, a procedure for the statistical verification and validation of a newly generated sorption isotherm M01 model is defined. A basic approach to the evaluation of a model for approximating experimental sorption data is presented. Based on the accuracy within an acceptable range, a model is considered valid for a set of experimental conditions conducive to its intended purpose. The matching of experimental data to the data obtained in the calculations was examined. Several statistical criteria, proposed in the literature, and indicators (the coefficient of determination (R2), the root mean squared error (RMSE) and the mean relative deviation (MRD)) were used for the quantitative verification of the newly generated sorption isotherm model. A qualitative statistical analysis was performed by the validation of statistical assumptions relative to the residuals obtained from the regression analysis. This was achieved by creating a normal quantile-quantile diagram with a normal residual distribution, and a Scatter plot diagram with a random residual distribution. Fitted with the newly generated three-parameter sorption isotherm model, the validation of the experimental data on the sorption isotherms of pear flesh tissue (determined at four temperatures 15˚C, 30˚C, 45˚C and 60˚C, and over a range of water activity from 0.110 to 0.920) was performed relative to the results of the Guggenheim, Anderson and De Boer (GAB) model. The success of the newly generated model was confirmed in relation to this reference model.